Perlindungan Konsumen Berbasis Kepastian Hukum di Indonesia Tentang Larangan Impor Pakaian Bekas - Iffatriansyah Soga; Weny Almoravid Dungga; Zamroni Abdussamad (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2024)
This research aims to determine the implementation of Minister of Trade Regulation No. 51/m-dag/per/7/2015 concerning the prohibition on imports of used clothing in Indonesia and the legal implications for consumer protection based on legal certainty in Indonesia. This research was conducted using a type of normative legal research with two types of approaches, namely the Statutory Approach and the Conceptual Approach. Based on research results, the implementation of Minister of Trade Regulation Number 51/M-DAG/7/2015 of 2015 concerning the prohibition on the import of used clothing is only limited to providing guidance and supervision and does not make recommendations to stop the business activities of trading imported used clothing to law enforcement authorities. The facts that occur in Indonesia state that there is still a lot of imported used clothing being bought and sold in markets and thrift shops, meaning that the implementation of the trade minister's regulations has not been implemented optimally. Legal Implications of the Implementation of Regulation of the Minister of Trade Number 51/M-DAG/PER/7/2015 concerning the Prohibition of Importing Used Clothes for consumer protection based on legal certainty gives rise to vague norms and conflict of norms which results in the absence of legal certainty. This is because the trade minister's regulations cause multiple interpretations and conflict with the finance minister's regulation number 6/PMK.010/2022, so that the rights and obligations to protect consumers are not guaranteed through these regulations.